Active harmonic filters: Control techniques review - Schwanz, Daphne; Bagheri, Azam; Bollen, Math; Larsson, Anders (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
The use of active filters for harmonic mitigation compensation is increasing together with the improvement of their control techniques. Depending on the situation, the use of one technique instead of the other makes the difference of achieving a better harmonic mitigation or not. In this paper, a review of control techniques related to harmonic filters for harmonic mitigation is presented, together with the advantages and disadvantages. From the literature review it was observed that new techniques are being used and classical ones are being improved.